Penggunaan Media Kantong Ajaib dalam Meningkatkan Kemampuan Mengenal Angka Anak Usia 4-5 Tahun - Ulfa, Mira; Yeniningsing, Taat Kurnita; Khoiriyah, Khoiriyah; Yuhasriyati, Yuhasriyati; Fauzia, Siti Naila (UIR PRESS, 2026)
The low ability of children aged 4-5 years in recognizing numbers in Nanggroe Pidie Jaya State Kindergarten is the background for this research. This research aims to improve children's ability to recognize numbers through the use of magic bag media. The method used is Classroom Action Research (CAR) or Classroom Action Research (CAR) with the Kemmis and McTaggart model which is implemented in three cycles, where each cycle includes the planning stage, action implementation, observation, and reflection. The research subjects were 15 children consisting of 6 boys and 9 girls. Data collection techniques were carried out through observation and documentation to see the development of children's abilities in naming, showing, and pairing numbers 1-10. The results of the study showed that children's ability to recognize numbers experienced a gradual increase, namely from 28.88% in the pre-cycle stage to 39.44% in Cycle I, increasing to 58.37% in Cycle II, and reaching 83.88% in Cycle III with the criteria of Very Good Development (BSB), thus exceeding the success indicator of 75%. Thus, the use of magic bag media has proven effective in improving the ability to recognize numbers in children aged 4-5 years at Nanggroe Pidie Jaya State Kindergarten.